Current and Emerging DMARDs for the Treatment of Rheumatoid Arthritis - Mysler E (Dove Medical Press, 2021)
Eduardo Mysler, Mariana Caubet, Ana Lizarraga Organización Medica de Investigación, Buenos Aires, ArgentinaCorrespondence: Eduardo Mysler Email e.mysler@omiargentina.com.arAbstract: Rheumatoid arthritis (RA) is the most prevalent form of inflammatory arthritis. It is a profoundly serious and severe disease that if it goes untreated could have severe consequences to the joints and health of the patient who carries this diagnosis. The treatment of RA has dramatically changed since the year 2000, with the discovery of the TNFis, then other biologics, and finally the JAKi. All these new medications with or without methotrexate in combination, tight control and treat to target have produced a revolution in the outcome of this disease. We reviewed and summarized the treatment options, and the most significant papers for each one of these new drugs. The reader could have a full picture with all the references of the recent publications. We also updated the biosimilar situation in RA, as well as the new drugs that will be coming to the market in the next 5 years.Keywords: rheumatoid arthritis, DMARDs, biosimilars